Mentiflufy: treinamento de meditação em estudantes surdos por meio de jogo controlado por interface cérebro-computador - Sales, Luana de Sousa (2025)
This study developed and evaluated a mind game for meditation training controlled by Brain-Computer Interface (BCI) in deaf students. The research involved eight deaf participants, who used the MENTIFLUFY platform for meditation exercises. This is an applied case study with quasi-experimental designs in a single group of participants, and with a qualitative approach. The data collected were analyzed based on the observation of the behavior of the variables for obtaining and interpreting results. Over the course of eight weeks, deaf students participated individually in weekly meditation sessions, mediated by the game monitored by BCI neurofeedback technology. Each student participated in two to three weekly sessions lasting 10 to 30 minutes. The game was developed based on specific guidelines for the creation of digital games for this audience, considering guidelines such as accessibility, incorporation of visual elements, intuitive and easy-to-use interface, and dispersion of auditory resources. During the training, positive and negative effects were observed in the participating students. Among the positive effects, the following stand out: increased engagement in school activities, improved emotional control, greater efficiency in concentration, and improved socialization. However, challenges were also identified, such as interference from external factors (noise and distractions) and the influence of conditions such as high levels of anxiety and fatigue, which affected the performance of some participants. The analysis of the results revealed that the continuity and regularity of the training were decisive for the success of the meditative practices, especially among the participants with the highest attendance. Thus, the results indicate a significant improvement in the meditation capacity of deaf students, suggesting that technology can be an effective tool for Mindfulness practices in this population. This study contributes to the ex- pansion of the use of ICC technologies in the educational and therapeutic context, providing insights into the integration of interactive games in the development of emotional self-regulation skills in deaf subjects. The findings of this study open possibilities for new investigations into the impact of neurofeedback and ICC-assisted meditation in the context of deafness, such as deaf adolescents with anxiety disorders.